The Lines That Held Us: Assessing Racial and Socioeconomic Disparities in SARS-CoV-2 Testing. (8th July 2021) - Hsiao, Chu J; Patel, Aditi G M; Fasanya, Henrietta O; Stoffel, Michelle R; Beal, Stacy G; Winston-McPherson, Gabrielle N; Campbell, Sean T; Cotten, Steven W; Crews, Bridgit O; Kuan, Kevin; Lapedis, Cathryn J; Mathias, Patrick C; et al.
Abstract: Background: Racial disparities in SARS-CoV-2 prevalence are apparent. Race is a sociocultural construct, necessitating investigation into how sociocultural factors contribute. Methods: This cross-sectional study linked laboratory data of adult patients between February 29 and May 15, 2020 with socio-demographics variables from the 2018 American Community Survey (ACS). Medical sites included healthcare organizations in Michigan, New York, North Carolina, California, Florida, Pennsylvania, and Washington. Race was treated as a proxy for racism and not biological essentialism. Laboratory data included patient age, sex, race, ethnicity, test result, test location, and residential ZIP code. ACS data included economic and educational variables contributing to an SES Index, population density, proportion Medicaid, and racial composition for corresponding ZIP code. Associations between race/socioeconomic variables and test results were examined using odds ratios (OR). Results: Of 126 452 patients [mean (SD) age 51.9 (18.4) years; 52 747 (41.7%) men; 68 856 (54.5%) White and 27 805 (22.0%) Black], 18 905 (15.0%) tested positive. Of positive tests, 5238 (SD 27.7%) were White and 7223 (SD 38.2%) were Black. Black race increased the odds of a positive test; this finding was consistent across sites [OR 2.11 (95% CI 1.95–2.29)]. When subset by race, higher SES increased the odds of a positive test for White patients [OR 1.10 (95% CI 1.05–1.16)] but decreased the odds for Black patients [OR 0.92 (95% CI 0.86–0.99)]. Black patients, but not White patients, who tested positive overwhelmingly resided in more densely populated areas. Conclusions: Black race was associated with SARS-CoV-2 positivity and the relationship between SES and test positivity differed by race, suggesting the impact of socioeconomic status on test positivity is race-specific.